Treatment of Philadelphia‐negative myeloproliferative neoplasms in accelerated/blastic phase with azacytidine. Clinical results and identification of prognostic factors. Issue 3 (30th May 2019) - Andriani, Alessandro; Elli, Elena; Trapè, Giulio; Villivà, Nicoletta; Fianchi, Luana; Di Veroli, Ambra; Niscola, Pasquale; Centra, Antonia; Anaclerico, Barbara; Montanaro, Guido; Martini, Vincenza; Aroldi, Andrea; et al.
Abstract: There have been some reports on a possible role of azacytidine (AZA) in the treatment of accelerated/blastic phase evolved from Philadelphia‐negative myeloproliferative neoplasms (MPN‐AP/BP), but results are conflicting. In this study, we analyzed a cohort of 39 patients with MPN‐AP/BP treated frontline with AZA at the standard dosage (75 mg/m 2 ). Median time from diagnosis to AP/BP evolution was 92.3 months (IR 29.9‐180.1). All patients were evaluable for hematologic response: two patients (5.2%) died early after AZA initiation, 13 patients (33.3%) had a progressive or stable disease, nine (23.1%) had a hematologic improvement (HI), seven (17.9%) achieved a partial response (PR), and eight (20.5%) a complete response (CR). Overall, 24 patients achieved a clinical hematologic response (HI + PR + CR), with an overall response rate of 61.5%. Median overall survival (OS) from AZA start of the whole cohort was 13.5 months (95% CI, 8.2‐18.7). There was no difference in median OS among patients with HI, PR, or CR ( P  = .908). These three subgroups as "responders" having been considered, a significantly better OS was observed in responder compared with nonresponder patients, with a median OS of 17.6 months (95% CI, 10.1‐25.0) versus 4.1 months (95% CI, 0.4‐10.0) ( P  = .001) Only female gender was significant for both achievement of response (.010) and OS duration ( P  = .002). In conclusion, AZA is useful for the management of MPN‐AP/BP, with an overall response rate (HI + PR + CR) of 61.5% and a longer OS in responders.